Intrinsic platelet reactivity before start with clopidogrel as predictor for on-clopidogrel platelet function and long-term clinical outcome - Hochholzer, Willibald; Valina, Christian M.; Bömicke, Timo; Amann, Michael; Stratz, Christian; Nührenberg, Thomas; Trenk, Dietmar; Neumann, Franz-Josef (Thrombosis and Haemostasis, 2015)
High on-clopidogrel platelet reactivity is associated with worse clinical outcome. Previous data suggest that intrinsic platelet reactivity before initiation of clopidogrel contributes significantly to on-clopidogrel platelet reactivity. It is unknown whether intrinsic reactivity can sufficiently predict on-clopidogrel reactivity and therefore identify patients with insufficient response to clopidogrel before initiation of treatment and at risk for worse clinical outcome. This analysis included 765 consecutive patients undergoing elective coronary stent implantation. Platelet reactivity was assessed by light transmission aggregometry (5 µM ADP) before administration of clopidogrel 600mg and after intake of first maintenance dose of clopidogrel on day 1 following coronary stenting. Patients were followed for up to seven years. The combined primary endpoint was death of any cause or non-fatal myocardial infarction. Intrinsic and on-clopidogrel platelet reactivity were significant correlated (r=0.31; p < 0.001). Among all tested clinical and genetic factors including the cytochrome P450 2C19*2 polymorphism, intrinsic platelet reactivity was the strongest predictor for on-clopidogrel platelet reactivity. However, intrinsic platelet reactivity could only explain 8 % of variability of on-clopidogrel platelet function. Only on-treatment platelet reactivity was predictive for long-term clinical outcome (HR 1.47, 95 % CI 1.05–2.05; p = 0.02) whereas intrinsic platelet reactivity was not (HR 1.03, 95 % CI 0.74–1.43; p = 0.86). In conclusion, intrinsic platelet reactivity before initiation of clopidogrel is the strongest predictor of early on-clopidogrel platelet reactivity but can only explain a minor proportion of its variability and is not significantly associated with clinical outcome. Thus, baseline testing cannot substitute on-clopidogrel platelet function testing.Clinical Trial Registration: ClinicalTrials.gov (Identifier: NCT00457236).
Keywords: Clopidogrel; platelet reactivity; risk prediction; mortality; coronary disease